How significant is upgrade in Gleason score between prostate biopsy and radical prostatectomy pathology while discussing less invasive treatment options?. (April 2014) - Suer, Evren; Gokce, Mehmet Ilker; Gulpinar, Omer; Gucal Guclu, Adil; Haciyev, Perviz; Gogus, Cagatay; Turkolmez, Kadir; Baltaci, Sumer
Abstract Objective.This study aimed to assess the oncological outcomes of patients experiencing an upgrade from their initial biopsy pathology, and to determine whether these tumours have characteristics resembling their initial biopsy Gleason score (GS) or final radical prostatectomy (RP) GS. Material and methods. Data on 632 patients undergoing open retropubic RP between January 1994 and May 2011 at Ankara University were investigated retrospectively. Data included age, preoperative prostate-specific antigen (PSA), clinical stage, biopsy GS, prostate volume, RP specimen GS, surgical margin positivity, pathological T stage and biochemical recurrence. Biochemical recurrence of GS concordant and upgraded tumours was compared. Results.GS concordance was found in 378 cases (59.8%) and GS upgrading was observed in 183 patients (28.9%). GS upgraded tumours were found to have higher biochemical recurrence rates than their corresponding concomitant GS group. Multivariate analysis revealed that serum PSA level, pathological T stage and GS upgrading were independent prognostic factors for biochemical recurrence. Age and prostate volume were not found to be independent prognostic factors. Conclusion. Upgrade in biopsy GS is a predictor for aggressive tumours with a higher risk for biochemical recurrence than concordant tumours. It may be observed in about a quarter of patients. As it was not possible to identify correctly those patients who may experience an upgrade in GS, patients who are candidates for less invasive treatment options must be informed about the risk of upgrading and the possibility of a worse clinical course.